LEGISLATIVE (REPRESENTATIVE) STATE AUTHORITIES OF SUBJECTS OF THE RUSSIAN FEDERATION AS AN OBJECT OF PUBLIC CONTROL - V. V. Grib (Сравнительная политика, 2016)
The purpose of the article is to give defi nition of legislative (representative) state authority of a subject of the Russian Federation and to analyze various forms of public control over the activity of the legislative (representative) state authority of a subject of the Russian Federation. Methodology: dialectics, analysis, synthesis, deduction, formal legal method, method of inter-sectoral legal researches. The key author’s conclusions are: Firstly, at the federal level, there has not been adopted so far a regulatory legal act fi xing the legal status of public councils under legislative (representative) state authorities of subjects of the Russian Federation, their main rights and obligations, procedure for their formation, and it, in its turn, shows major defi ciencies on the legislator’s part. However, a number of regional legislators have made an attempt to independently settle the issue of formation of public councils under legislative (representative) state authorities of subjects of the Russian Federation by fi xing the relevant provisions in special regional laws on public control bases in a subject of the Russian Federation. Secondly, many regulatory legal acts adopted at regional level, fi xing the procedure for recall of deputies of representative authorities of a subject of the Russian Federation, are recognized, as of today, by judicial authorities as partly invalid or void. Thirdly, the forms of public control mentioned in the article are not of exhaustive nature and can be expanded by relevant lawful subjects of the Russian Federation, but these forms of public control, at their effi cient and combined application, can be an effi cient instrument for control over power on the part of civil society. Scientific and Practical Importance. The conducted research develops and specifi es forms of public control. As exemplifi ed by various forms of public control over activity of legislative (representative) state authority of a subject of the Russian Federation, revealed were defi ciencies on the legislator’s part, preventing efficiency of legal regulation.